The influence of government budgets for anti-corruption efforts and government effectiveness on national transparency levels - Supawadee Moss; Wonlop Writthym Buachoom (Journal of Public Budgeting Accounting & Financial Management, 2026)
Purpose This study examines government budgeting for anti-corruption organisations and its ability to increase transparency and reduce corruption in Thailand. It also considers government effectiveness (GE), control of corruption (CC), regulatory quality (RQ), voice and accountability, political stability and military spending (MS) as factors influencing greater national transparency. Design/methodology/approach With the quantitative approach, the linear regression is applied to test the relationship between related budgeting factors and the level of transparency (LT). Data included in the study were collected for 20 years, ranging from 2003 to 2022. The data related to the budget allocated are manually collected from the annual report of the National Anti-Corruption Commission (NACC) and the Office of Public Sector Anti-Corruption Commission (PACC), while some indicators are collected from the global economy and World Bank databases. Findings The findings suggest that budget spending on anti-corruption organisations is negatively associated with transparency. This is not surprising in a developing country, where increased government spending alone can lead to a higher rate of corruption due to the opportunities it creates for misusing public funds and the potential inefficiencies of the organisations. However, when combined with high GE, budget spending becomes more effective in increasing transparency. This suggests that budget spending alone does not reduce corruption; it must be paired with effective governance. The findings also indicate that greater political instability and higher MS correlate with lower transparency, particularly when military oversight is weak. Conversely, stronger RQ enhances transparency. Research limitations/implications Limitations of this research include the unavailability of disaggregated anti-corruption budget data (HL and ML) outside Thailand, which precluded direct replication of the core model in the SEA sample. Our fixed-effects approach controlled for unobserved, time-invariant heterogeneity and global shocks, but finer-grained variables, such as enforcement capacity, media freedom or civil-society strength could further illuminate the mechanisms at work. Practical implications Practical implications suggest that policy prescriptions cannot rely solely on increased funding or regulatory design. They must strengthen institutional capacity and accountability to translate resources into genuine transparency gains. Originality/value As the effectiveness of budget allocation in reducing corruption, especially in developing countries like Thailand, remains questionable, this study highlights literature to document the effectiveness of the budget system in increasing the transparency level of government activities. The study also extends to test the effectiveness of budgeting on Southeast Asian countries, including Brunei, Cambodia, Laos, Malaysia, the Philippines, Singapore and Vietnam. The results add to the literature that GE and higher CC help to increase the LT in these countries.
Keywords: Corruption and Economic Development; Taxation and Compliance Studies; E-Government and Public Services